“Everyone in my immediate family…”: Students’ Experiences with Suicide - Toni Gallegos; Regina Praetorius; Zoya Chaturvedi (Journal of Social Work Education and Practice)
Background: Suicide is a prevalent issue that is faced across the life span and has been found to be the third leading cause of death in those aged 10 to 34 years old. As social workers working with clients who have faced suicidal ideation or experienced it in their life. As it stands there is a lack of social work education on suicide in curriculum in BSW and MSW programs.